ANALISIS KESTABILAN LERENG JALAN TAMBANG DI PT. SUMBAR CALCIUM PRATAMA JORONG ATAS HALABAN, NAGARI HALABAN, KECAMATAN LAREH SAGO HALABAN, KABUPATEN LIMA PULUH KOTA, PROVINSI SUMATERA BARAT - Rully Septian; Bambang Heriyadi; Heri Prabowo (Journals Mining Engineering : Bina Tambang, 2018)
mining area. Planning of the slope geometry will be used by Bishop Simplified and Hoek and Bray methods.Initial data Clay: Unit Wight (γ) = 19.67 kN / m3, Cohesion (c ') = 32.17 kN/ m2 and internal angle (φ') = 39.11 °. The initial slope height is 14.543 meters and overall angle of the slope is 51 °.Geometry of slope recommendation: 1. Bishop Simplified method of saturated condition FK 0.984 witch mean slope is insecurity, reduction of slope angle from 51 ° to 42 °, FK 1,324 slope in safe state. 2. Method Hoek and Bray saturated conditions FK 1.25 Unsafe slope, slope angle from 51 ° to 42 °, then FK 1.41 slope in safe condition.Keywords: initial geometry, bishop simplified, hoek and bray, security factor